2014
DOI: 10.1002/ijc.29097
|View full text |Cite
|
Sign up to set email alerts
|

A mesenchymal‐like phenotype and expression of CD44 predict lack of apoptotic response to sorafenib in liver tumor cells

Abstract: The multikinase inhibitor sorafenib is the only effective drug in advanced cases of hepatocellular carcinoma (HCC). However, response differs among patients and effectiveness only implies a delay. We have recently described that sorafenib sensitizes HCC cells to apoptosis. In this work, we have explored the response to this drug of six different liver tumor cell lines to define a phenotypic signature that may predict lack of response in HCC patients. Results have indicated that liver tumor cells that show a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 47 publications
5
98
0
Order By: Relevance
“…Some tissue markers, such as ␣␤-crystallin (35), FGF3/FGF4 (36), JNK (37), and pERK (38) have been reported to predict sorafenib response. A recent study indicated that a mesenchymal profile and expression of CD44 may predict lack of response to sorafenib in HCC patients (39). Although various markers have been studied, identifying predictive biomarkers to sorafenib response remains challenging and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Some tissue markers, such as ␣␤-crystallin (35), FGF3/FGF4 (36), JNK (37), and pERK (38) have been reported to predict sorafenib response. A recent study indicated that a mesenchymal profile and expression of CD44 may predict lack of response to sorafenib in HCC patients (39). Although various markers have been studied, identifying predictive biomarkers to sorafenib response remains challenging and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is postulated that sorafenib resistance is closely correlated with the dynamic changes of numerous molecules, especially their up-or down-regulated expression, involved in the mutual transition between epithelial and mesenchymal cell phenotypes and various signaling pathways. Particularly, epithelial cells are more susceptible to a Raf kinase inhibitor, sorafenib, whereas mesenchymal cells showed significant resistance [68,69]. In addition, PI3K/Akt showed higher activity and integrin-linked kinase (ILK) exhibit in the mesenchymal cells as compared to epithelial cells [70,71].…”
Section: Epithelial-mesenchymal Transitions (Emt)mentioning
confidence: 98%
“…Beyond linked expression, CD44 actively promotes EMT (Cho et al, 2012; Ju et al, 2014; Nevo et al, 2014; Wang D. et al, 2014; Yu D. et al, 2014; Fernando et al, 2015; Jiang et al, 2015; Shang et al, 2015; Wang et al, 2015), e.g., by inhibiting E-cadherin-β-catenin complex formation accompanied by β-catenin translocation to the nucleus (Li and Zhou, 2011). There is evidence that Notch plays a central role.…”
Section: Linking Cd44/cd44v6 Activities To Cic Featuresmentioning
confidence: 99%